Gender assessment of the agricultural sector in the Democratic Republic of the Congo - Ragasa, Catherine; Kinwa-Muzinga, Annie; Ulimwengu, John M. (International Food Policy Research Institute, 2012)
Based on the 2011 Global Hunger Index, the Democratic Republic of the Congo (DRC) has the most severe level of hunger and malnutrition. There is growing recognition that development in the agriculture sector and increasing productivity will be critical to reverse this trend. A growing set of literature looks at gender disparity in access to critical inputs, knowledge and markets, which have been shown to contribute to low productivity and nutrition insecurity. This assessment contributes to the knowledge gap by compiling existing empirical evidence and investigating the gender gaps in access to resources and opportunities in the agriculture and food sector in the DRC.